PENGARUH KRONOFARMAKOLOGI TERHADAP KADAR KOLESTEROL TOTAL DAN TRIGLISERIDA DALAM DARAH PASIEN PENGGUNA OBAT GOLONGAN STATIN DAN FIBRAT - Resna Sari Asih; Ilham Alifiar; Yedy Purwandy (JFL : Jurnal Farmasi Lampung, 2020)
ABSTRACT Chronopharmacology is a therapy based on circadian rhythms that can be said to be relevant if the risk and symptoms of the disease are predicted to vary over time. This study aims to determine the effect of chronopharmacology on total cholesterol and triglyceride levels in the blood of patients with fibrates and statin groups, so that patients with certain diseases are encouraged to take drugs according to the organ picket hours or circadian rhythms. This study was an observational descriptive study with a cross sectional study design involving 18 patients. Primary data were obtained through interviews and checking total cholesterol and triglyceride levels while secondary data were obtained from the patient's medical record. Based on the results of the analysis using SPSS for statin drug use in the morning and at night getting a value of P = 0.003. whereas for drug use in the fibrat group in the morning and evening, P = 0.083 was obtained. Based on the results of the research that has been done, it can be concluded from 18 patients using statins and fibrates in RSUD Dr. Soekardjo Tasikmlaya, for the use of statin drugs at night is more beneficial, but in the use of fibrates in the morning or evening the same effectiveness. Keyword : chronopharmacology, statin, fibrat